Implementation of an internal check of oral oncolytics: a single-center, specialty pharmacy safety initiative. (3rd September 2019) - Hughes, Mitchell; Kriska, Richard; Strong, Gregory; Chung, Jennifer; Nguyen, Lily; Rubin, Daniel; Murphy, Melissa; Favatella, Joseph; Capozzi, Donna
Abstract: Background: Oral oncolytic therapies (OOT) for patients with cancer continue to pose unique safety challenges. Unlike infusion therapies, there are few best practice recommendations for checking OOT. A multicenter review of four oncology clinics in the United States, estimated 8.1 errors in medications per 100 clinic visit identified. 1 The American Society of Health-System Pharmacists identify administration and ordering were the most common phases of the medication-use process where errors occur. 2 Despite the high-risk nature of OOT and high error-rate in these particular phases, with pharmacist surveillance, there continues to be little consensus for oral oncolytic safety to guide specialty pharmacists (SPs). Aims: The objectives of this single-center, quality improvement study was to review the quality metrics of the implementation of an oral oncolytic check process, in the specialty and ambulatory setting as a method to enhance medication safety and improve vigilance. Methods: The study was approved by the Institutional Review Board at the Hospital of the University of Pennsylvania. A standardized check process and documentation of capecitabine and temozolomide was implemented beginning in December 2016 for an adult oncology population. SPs have direct communication to pharmacy specialists and provider teams through the electronic medical record via Epic. Upon receipt of a new prescription, the SP reviews the prescription for: prescriber, chemotherapy regimen, indication, body surface area, dose verification, appropriate day supply/refills, laboratory values, allergy evaluation, drug interactions, and pre-medications. The SP documents this review as an intervention in Epic for every capecitabine and temozolomide prescriptions before processing. Intervention data between December 2016 and September 2018 was queried and quantified. Results: Over 22 months, a total of 1, 619 intervention documents were reviewed with 551 intervention documents requiring intervention (34%). A total of 639 actionable interventions were identified. The top three categories were missing pre-medications (54.1%), missing/abnormal laboratory results (19.6%), and drug-drug interactions (13.6%). Rare interventions included dose clarification requests (3.6%), dose change requests (1.4%), and quantity supply requests (2.7%). A SP referred to a pharmacy specialist or provider outside of Epic communication in 21.2% of cases and 3.7% of cases respectively. The average time by the SP per intervention was 12.1 minutes (Range: 10-45 minutes). Conclusions: OOT is exponentially growing with unique risks associated when prescribing, with the SP being the last line of defense. Implementing an internal checking tool of oral oncolytics creates a standardized safety check and promotes active communication with oncology care teams. Addition of all OOT to incorporate mandatory documentation is ongoing.